Boundary Conditions for Combustion Field and LB Simulation of Diesel Particulate Filter (Communications in Computational Physics, 2020)
A diesel particulate filter (DPF) is a key technology to meet future emission standards of particulate matters (PM), mainly soot. It is generally consists of awall-flow type filter positioned in the exhaust stream of a diesel vehicle. It is difficultto simulate the thermal flow in DPF, because we need to consider the soot deposition and combustion in the complex geometry of filter wall. In our previous study,we proposed an approach for the conjugate simulation of gas-solid flow. That is, thegas phase was simulated by the lattice Boltzmann method (LBM), coupled with theequation of heat conduction inside the solid filter substrate. However, its numericalprocedure was slightly complex. In this study, to reduce numerical costs, we havetested a new boundary condition with chemical equilibrium in soot combustion at thesurface of filter substrate. Based on the soot oxidation rate with catalysts evaluatedin experiments, the lattice Boltzmann simulation of soot combustion in the catalyzedDPF is firstly presented to consider the process in the after-treatment of diesel exhaustgas. The heat and mass transfer is shown to discuss the effect of catalysts.